Consumption Recovery, Digital Economy and Green Transformation in the Post-Pandemic Era - Lyu, Wenbo; Qian, Yanfei; Zhang, Keming; Han, Fangping; Wang, Yiqian (Theoretical Key Issues and Practical Development Trends of China’s Digital Economy, 2024)
This paper examines the dynamics of consumption recovery, the digital economy, and green transformation in the post-pandemic era. Drawing insights from Singapore and Hong Kong, a framework for evaluating recovery patterns in the consumption sector was proposed. The findings reveal both temporal and spatial trajectories of consumption recovery, initially favoring high-end tourism before shifting towards local services. To enhance understanding, a sensory-based classification of consumption with six dimensions was introduced: Tasting, Seeing, Hearing, Touching, Smelling, and Mixed Senses. This classification shows distinct valuation weights among these categories; Seeing and Hearing rank highest. Digital consumption's critical role as a catalyst for sector growth was highlighted. To quantify this impact effectively, a digital consumption index was proposed alongside indices for digital RMB and China’s unique digital economy model—offering nuanced insights into how digital consumption drives economic expansion. Our analysis of China's 2022 economic performance combined with 2023 government policies illustrates that digital consumption can upgrade consumer behavior while representing higher valuation targets. Middle- to high-income groups have shown resilience in spending habits; however, significant untapped potential exists among lower-income demographics—especially farmers—for future growth. To leverage this potential, strategies to enhance income levels and expenditure capabilities among farmers through digital RMB vouchers were recommended while addressing their specific high-consumption needs. The research emphasizes tackling income disparities while guiding upgrades across all income brackets—particularly within lower-income segments—to facilitate sustainable economic recovery. In conclusion, this paper offers an integrated perspective on consumption recovery by incorporating sensory classifications along with indices related to digital engagement and green transformation strategies. The findings provide valuable insights for policymakers, investors, and researchers aiming to cultivate a more inclusive economic landscape post-pandemic.